A Review of Conventional and Emerging Process Technologies for the Recovery of Helium from Natural Gas - Thomas E. Rufford; K. Ida Chan; Stanley H. Huang; Eric F. May (Adsorption Science & Technology)
Helium is a unique gas with a wide range of important medical, scientific and industrial applications based on helium's extremely low boiling temperature, inert and non-flammable nature and small molecular size. The only practical sources of helium are from certain natural gas (NG) fields. As world demand for helium rapidly increases, the value of NG fields that contain it even in very small amounts is likely to rise significantly if the helium can be recovered efficiently. However, recovering the helium from the NG using conventional cryogenic distillation processes is expensive and energy intensive. We review the scope for improving the efficiency of the conventional helium recovery and upgrade processes, and evaluate the potential of emerging technologies based on adsorption or membrane separations for helium upgrade and purification. Helium recovery and purification processes are comparable in many ways with systems designed for hydrogen purification and thus, many of recent technological advances for H 2 separation from CH 4 N 2 and CO 2 may be applicable to a helium recovery process. Furthermore, some recent patents and pilot plant studies indicate there exist several opportunities for the development of advanced materials, such as helium-selective adsorbents, and optimized process operations for the recovery of helium from NG.